Stochastic Nonlinear Beam Equations with Lévy Jump (Communications in Mathematical Research, 2021)
In this paper, we study stochastic nonlinear beam equations with Lévyjump, and use Lyapunov functions to prove existence of global mild solutions andasymptotic stability of the zero solution.